GAGASAN PENERAPAN PAJAK PROGRESIF DALAM PEMUNGUTAN JENIS PAJAK BUMI DAN BANGUNAN - Wahyudi, Dedy (Katalogis, 2015)
This study aims to determine the application of the Progressive Tax on Land and Building Tax type is already in line with the principles of fair tax collection and to identify and find the concept of applying Progressive Tax on Land and Building Tax types.Â This research is a normative law by using the approach of legislation, and conceptual approaches. Primary and secondary legal materials were used in this study were collected through literature, which is seeking and legal material to browse the inventory of documents, literature books, law journals, and legislation related to the object of research. Legal materials that have been obtained are described and presented descriptively and analytically deduced by using the deductive method.Â The results showed that the application of progressive tax types Land Tax Building Rural and Urban (PBB-P2), it must be stated in the form of local regulation as the legal basis for implementation, the era of regional autonomy open areas can expand the tax base and its authority in the determination of tariffs under the Act No. 28 Year 2009 on Regional Taxes and Levies. The ability to fund their spending needs even greater because the area can easily adjust earnings in line with an increase in the local tax base and discretion in setting the rates. where the application of a progressive tax on the kind of property taxes on the one hand can potentially increase revenue which are levied in accordance with the principles of justice and on the other hand at the same moment also has the potential burden on society that allows the collection do not meet the principles of justice. This progressive tax in addition to increasing revenue (budgetary function), can also limit and maintain the balance of land ownership and utilization (function regurelend) for the greatest welfare of the community.